Sistem Pendukung Keputusan Menggunakan Metode Simple Additive Weighting (SAW) Untuk Program Bantuan Langsung Tunai Pasca Covid-19 Pada Desa Lais - Rama Andriya Saputra; Widya Cholil (Journal of Software Engineering Ampera, 2021)
The village Fund Diret Cah Assistance (BLT-DD) is a from of financial assistance to poor families in the village sourced from the village found so that it is expected to reduce the impact COVID-19 pandemic. The village  found BLT in Lais village itself does not escape several obstacles, such as the lack of community evaluation to so that delivery of the village found BLT is not on target which usually does not refer to the criteria for poor families. So the problem faced  is how to determine the recipients of the village fund BLT so that is more targeted and accepted by the people who need it more. The criteria used as a reference in making decisions. This SAW calculation will later be implemented into a web using MySQL.